From conception to recruitment: Nutritional condition of the dam dictates the likelihood of success in a temperate ungulate - Lamb, Sydney; McMillan, Brock R.; van de Kerk, Madelon; Frandsen, Paul B.; Hersey, Kent R.; Larsen, Randy T. (Frontiers in Ecology and Evolution, 2023)
Maternal effects are the influence of maternal phenotype and the maternally-provided environment on the phenotype (i.e., expression of traits) of offspring. Frequently, maternal effects are manifest both before and after parturition. Pre-parturition effects are primarily direct allocation of energy to the offspring that is in utero. Post-parturition effects can include direct (e.g., nursing and defending offspring) and indirect (e.g., selection of habitat that is relatively safe or has high nutritional value) influences. While both direct and indirect effects are often discussed, there is a paucity of information on the relative importance of each type on offspring due to the difficulty in monitoring mothers prior to parturition and mother-offspring relationships after parturition in free-ranging animals. Our objective was to determine the importance of direct maternal effects on birth weight, growth rates, and survival of mule deer (Odocoileus hemionus) fawns from birth through the first 18 months of life. We determined the effect of nutritional condition of the dam (mother) on birth weight (pre-parturition direct effect). We also examined the post-parturition direct effect of dam nutritional condition on growth rates and survival of fawns. Direct maternal effects were evident both before and after parturition; dams in better nutritional condition produced offspring with greater mass at birth, higher rates of growth, and increased survival. Our findings demonstrate that maternal nutritional condition influences fawn health from gestation through recruitment. These links highlight the importance of considering direct maternal effects when examining population dynamics and reproductive success in long-lived mammals. Management plans for ungulates should include assessment of nutritional condition of adult females to maximize likelihood of effective conservation.